Phthisiology questions in International Congress of the European Respiratory Society 2019: achievement of the Ukrainian scientists - M. I. Gumeniuk; G. L. Gumeniuk; D. O. Butov; S. H. Opimakh (Civic Union "Communicable Diseases Intensive Care Association", 2019)
Abstract. The program of the International Congress of the European Respiratory Society (ERS) in 2019 covered the key topics of respiratory medicine. One of Congress's leading issues has been tuberculosis, which is one of the world's major threats to humanity. Since 1995, WHO has documented a TB epidemic in Ukraine and today this problem is urgent in our country. Aim. To analyze tuberculosis information at the 2019 ERS International Congress, with a summary of the phthisiology abstracts presented by Ukrainian scientists at this event. Materials and methods. The data regarding the abstracts of scientific reports were obtained from the Congress website and the online program of the personal account of an ERS member, doctor of medical sciences, professor Gumeniuk Galyna. Results. Tuberculosis issues were discussed daily in Congress in the form of symposia, expert meetings, thematic and poster discussions and oral presentations. In total, 201 short messages were addressed at the 2019 ERS Congress of Phthisiology, including 7 abstracts (3.5 %) owned by Ukrainian scientists. Conclusions. Ukrainian phthisiologists actively participated in the work of the Congress ERS 2019. Topics presented by national scientists reports (epidemiology, treatment of tuberculosis with drug resistance, including patients with HIV infection, predicting the effectiveness of treatment, prevention of adverse events and concomitant to tuberculosis disorders) meets the global challenges of tuberculosis in the world.